Factors Affecting the Distribution of Consumer Segment Financing and Its Implications on the GRDP of the Financial Services and Insurance Sector as well as MSME Empowerment in Indonesia - Nani Almuin; Pudji Astuty (PT. ALHAFI BERKAH INDONESIA, 2025)
Examining the variables affecting consumer financing distribution and its effects on the GDP of the insurance and financial services industries, as well as the empowerment of Micro, Small, and Medium-Sized Enterprises (MSMEs) in Indonesia, are the goals of this study. Panel data regression analysis is the methodology employed in this study. The data utilized consist of panel data from 15 provinces with the best performance in Islamic bank financing, based on reports registered at the Financial Services Authority (OJK), encompassing a ten-year span from 2014–2023. The study's findings show that the distribution is positively and significantly impacted by Third Party Funds (DPK), inflation, the number of Islamic banks, and digital transactions of Islamic financing for the consumer segment. Furthermore, the distribution of Islamic financing positively influences the GRDP of the financial services and insurance sector and MSME empowerment in Indonesia.